2015
DOI: 10.1093/icvts/ivv368
|View full text |Cite
|
Sign up to set email alerts
|

Optimal timing for early surgery in infective endocarditis: a meta-analysis

Abstract: To systematically review early surgery and the optimal timing of surgery in patients with infective endocarditis (IE), a search for foreign and domestic articles on cohort studies about the association between early surgery and infective endocarditis published from inception to January 2015 was conducted in the PubMed, EMBASE, Chinese Biomedical Literature (CBM), Wanfang and Chinese National Knowledge Infrastructure (CNKI) databases. The studies were screened according to the inclusion and exclusion criteria, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 32 publications
1
24
1
2
Order By: Relevance
“…Transplantation* (3 kidney, 1 heart, 1 bone marrow). Postponed: conducted ≥1 month of hospitalization first 2 weeks rather than later in cases of native IE (OR = 0.46, 95% CI [0.31, 0.69]; p = 0.001) but not in cases of prosthetic IE (OR = 0.83, 95% CI [0.65, 1.06]; p = 0.413) [37]. Another study found no reduction in one-year mortality in patients with S. aureus IE on prosthetic valve when the surgery was performed during the first 60 days of hospitalization rather than later (risk ratio, 0.67 [95% CI: 0.39-1.15]; p = 0.15).…”
Section: Discussionmentioning
confidence: 99%
“…Transplantation* (3 kidney, 1 heart, 1 bone marrow). Postponed: conducted ≥1 month of hospitalization first 2 weeks rather than later in cases of native IE (OR = 0.46, 95% CI [0.31, 0.69]; p = 0.001) but not in cases of prosthetic IE (OR = 0.83, 95% CI [0.65, 1.06]; p = 0.413) [37]. Another study found no reduction in one-year mortality in patients with S. aureus IE on prosthetic valve when the surgery was performed during the first 60 days of hospitalization rather than later (risk ratio, 0.67 [95% CI: 0.39-1.15]; p = 0.15).…”
Section: Discussionmentioning
confidence: 99%
“…The mortality of patients who underwent surgery was almost one-sixth of that of patients who did not undergo surgery in our study. Several previous studies pointed out that surgery was independently associated with a lower risk of inhospital mortality [13] [14,15] . We previously performed a multivariate analysis in 313 cases of IE (including prosthetic valve endocarditis) [11] and identi ed intravenous drug addiction, prosthetic valve endocarditis, hemorrhagic stroke, acute congestive heart failure, renal insu ciency, left-sided endocarditis, and early surgery as independent predictors of in-hospital mortality.…”
Section: Factors Related To the False-negative Tte Resultsmentioning
confidence: 99%
“…Early surgery has been proved to be associated with a significantly lower in-hospital mortality rate as compared to medical therapy [49,50] Mortality of patients who underwent surgery was one sixth of that of patients who did not have the surgery. In our study, up to 59.7% of our patients underwent surgery during hospitalization, which is similar to other regions like Brazil (52.4-55.0%) [43] , Spain (57.0%) and…”
Section: Risk Factors For In-hospital Mortalitymentioning
confidence: 99%